Development of microbial geotechnology in Singapore - Chu, Jian; Ivanov, Volodymyr M.; He, Jia; Li, Bing; Naemi, Maryam; Stabnikov, Victor (My University, 2011)
Both nature processes and laboratory studies have shown that microorganisms can be used to improve the engineering properties of soil. As such, it is possible to develop methods that utilize the microbial process to treat soil in a way similar to that of cement. When more knowledge is accumulated through research findings and technology development, a new branch of geotechnical engineering – the Microbial Geotechnology can be established. The Microbial Geotechnology can have the following three applications: (a) biocementation to increase the strength of soil, (b) bioclogging to reduce the permeability of soil, and (c) biogas to increase the liquefaction resistance of sandy soil. Some types of microorganisms or bioprocesses that may contribute to the biocementation, bioclogging or biogas effects are identified and discussed. Some experimental data are presented to show that the permeability of sand can be reduced by four orders of magnitude and the strength of sand can be increased to a substantial value after the soil has been treated using bacteria. However, the whole study still stays at the laboratory stage and much more efforts are required to turn this scientific idea into viable technologies
Keywords: biocementation; bioclogging; біоцементація; біозаповнення ґрунтових пір; биоцементация; биозаполнение почвенных пор; кафедра біотехнології і мікробіології